KARAKTERISTIK MOROMI DAN KECAP MANIS SERTA KAJIAN AKTIVITAS ANTIOKSIDANNYA (Jurnal Teknologi Pangan, 2013)
Antioxidants are compounds that can retard oxidation in food. Antioxidants should be able  to  delay  or  prevent  the  occurrence  of  autooksidasi  reaction  of  free  radicals  in  lipid. Compounds that act as antioxidants in moromi and soy sauce  is mainly caused by the Maillard reaction  product  compounds.  Protein,  alpha-acids  and  phenols  compound  that  can  be potentially as an antioxidant, in this study haven’t showed antioxidant activity. In the soysauce products  has  the  ability  capture  the  DPPH  radical  more  strongly  on  the  fraction  with molecular  weight  30  kDa  to  greater  than  100  kDa  and  its  activity  similar  to  vitamin  C  200 ppm, whereas the inhibition of fatty acid oxidation was stronger in the fraction with molecular weight <10 kDa to 30 kDa and its activity is greater than 200 ppm BHT.Key Words : Maillard Reactions,moromi, soysauce, antioxidative activity